Sources of stress and the coping style among trainees teacher in the teacher training colleges in Johor, Malaysia - Yahaya, Azizi; Abd. Ghaffar, Mohd. Najib; Ismail, Sharifudin; Ramli, Jamaluddin (2002)
Stress has become part & parcel of the human life. Human beings cannot avoid from being Human beings cannot avoid from being stressed. In fact stress has become a necessity in human life. Selye (1956) points out that no human beings can survive without stress. Stress can be either positive or negative. In the case of positive stress (eustress) it act as a motivating factor that enhances achievements whereas negative stress (distress) involves strain, tension and burnout physically and psychologically. Moderate amounts of stress help motivate us and, at times, increase our performance (Moore, Burrows & Dalziel,1992). The amount of stress experienced may be influenced by the individuals ability to effectively cope with stressful events and situations (D Zurilla & Sheedy stressful events and situations (D Zurilla & Sheedy, 1991). Patterson and McCubbin (1987) found that a good Patterson and McCubbin (1987) found that a good coping response helps to promote individual growth.